2014
DOI: 10.1074/jbc.m113.523621
|View full text |Cite
|
Sign up to set email alerts
|

Ovalbumin Modified with Pyrraline, a Maillard Reaction Product, shows Enhanced T-cell Immunogenicity

Abstract: Background: Maillard reaction (MR) modifies food allergens with various glycation structures during thermal processing of foods. Results: We show that pyrraline, a glycation structure, enhances potential allergenicity of ovalbumin, a model allergen, by promoting scavenger receptor class A-mediated allergen uptake by dendritic cells. Conclusion: Pyrraline could act as a pathogenesis-related component in food allergies. Significance: We reveal how MR links to food allergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 41 publications
5
71
0
3
Order By: Relevance
“…On the other hand, a reduced digestibility of modified milk proteins may affect the allergic response to specific dairy products; in fact, it has been reported that proteins resistant to digestion may behave as major food allergens [55,56]. Extensive glycation/ glyco-oxidation of surface-exposed residues in specific milk proteins should also per se modulate the allergenic impact of these nutrients [26,57,58].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, a reduced digestibility of modified milk proteins may affect the allergic response to specific dairy products; in fact, it has been reported that proteins resistant to digestion may behave as major food allergens [55,56]. Extensive glycation/ glyco-oxidation of surface-exposed residues in specific milk proteins should also per se modulate the allergenic impact of these nutrients [26,57,58].…”
Section: Resultsmentioning
confidence: 96%
“…Shotgun analysis characterized a variable number of lactosylation sites within each protein; their number increased with harder milk processing conditions. This may lead to a progressive decrease of the milk nutritional value, as it reduces the bioavailability of essential amino acids, and may affect function, digestibility and allergenic potential of individual proteins [14,23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…). For instance, the effects of MR on immunogenicity and allergenicity of food allergen OVA have also been studied and have shown an elevated risk of food allergy . We aimed to describe how glycation reaction of the major milk allergen, BLG, influences handling and processing by epithelial and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction leads to the modification of proteins with various types of glycation structures. Importantly, glycated OVA induced higher allergen-specific CD4 + T cell responses and IgE production in mice, compared to native OVA [51], suggesting that SR-A transfers its ligands to MHC class II loading pathway in APCs to promote CD4 + T cell activation. SR-A structurally comprises the transmembrane domain, a spacer region, a helical coiled coil domain, a collagenous domain and a C-terminal cysteine-rich domain [52].…”
Section: Scavenger Receptorsmentioning
confidence: 99%